A Reduction in Maximal Incremental Exercise Test Duration 48 h Post Downhill Run Is Associated with Muscle Damage Derived Exercise Induced Pain - Chrismas, Bryna C. R.; Taylor, Lee; Siegler, Jason C.; Midgley, Adrian W. (Frontiers in Physiology, 2017)
Purpose: To examine whether exercise induced muscle damage (EIMD) and muscle soreness reduce treadmill maximal incremental exercise (MIE) test duration, and true maximal physiological performance as a consequence of exercise induced pain (EIP) and perceived effort. Methods: Fifty (14 female), apparently healthy participants randomly allocated into a control group (CON, n = 10), or experimental group (EXP, n = 40) visited the laboratory a total of six times: visit 1 (familiarization), visit 2 (pre 1), visit 3 (pre 2), visit 4 (intervention), visit 5 (24 h post) and visit 6 (48 h post). Both groups performed identical testing during all visits, except during visit 4, where only EXP performed a 30 min downhill run and CON performed no exercise. During visits 2, 3, and 6 all participants performed MIE, and the following measurements were obtained: time to exhaustion (TTE), EIP, maximal oxygen consumption (V·O2max), rate of perceived exertion (RPE), maximum heart rate (HRmax), maximum blood lactate (BLamax), and the contribution of pain to terminating the MIE (assessed using a questionnaire). Additionally during visits 1, 2, 3, 5, and 6 the following markers of EIMD were obtained: muscle soreness, maximum voluntary contraction (MVC), voluntary activation (VA), creatine kinase (CK). Results: There were no significant differences (p ≥ 0.32) between any trials for any of the measures obtained during MIE for CON. In EXP, TTE decreased by 34 s (3%), from pre 2 to 48 h post (p < 0.001). There was a significant association between group (EXP, CON) and termination of the MIE due to “pain” during 48 h post (χ2 = 14.7, p = 0.002). Conclusion: EIMD resulted in premature termination of a MIE test (decreased TTE), which was associated with EIP, MVC, and VA. The exact mechanisms responsible for this require further investigation.